ANALYSIS OF PUBLIC RELATIONS CODE OF ETHICS IN THE FILM AIR 2023 - Armawati, Dea; Rochmania, Ainur (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to examine how the PRSA (Public Relations Society of America) Code of Ethics principles are represented in the film Air (2023), which depicts the communication strategies between Nike and Michael Jordan in establishing brand image. Method: Using a descriptive qualitative approach, data were collected through detailed scene observation and supporting theoretical documentation. The analysis employed stages of data reduction, presentation, and conclusion to identify ethical values embedded in character interactions and narrative development. Results: The findings indicate that the six PRSA principles—advocacy, honesty, expertise, independence, loyalty, and fairness—are consistently reflected in the film, particularly through the communication strategies and decision-making processes of Sonny Vaccaro and Deloris Jordan. These portrayals illustrate the role of ethics in fostering credibility, building reputation, and maintaining public trust within professional Public Relations practice. Novelty: This research contributes to the intersection of media studies and public relations ethics by demonstrating how cinematic narratives can serve as a medium to analyze and contextualize ethical practices, offering insights for both academic discourse and professional application in the communication field.